The influence of contrived motivating operations on social discounting: Relative economic hardship affects choice. Issue 2 (29th January 2019) - Belisle, Jordan; Dixon, Mark R.; Rowsey, Kyle E.
Abstract : Thirty‐six participants were given three social discounting surveys, and each survey was preceded by one of three contrived hypothetical scenarios. In each scenario, the participant was asked to consider situations in which either the participant (SELF), a hypothetical other (OTHER), or both the participant and the hypothetical other (BOTH) were experiencing economic hardship (i.e., needed money to avoid a negative outcome). Results replicate previous research suggesting that the probability of participants foregoing the money decreased across social distance in the BOTH and OTHER conditions; however, no discounting was observed for median responses in the SELF condition. In addition, the highest area under the curve and lowest s values were associated with the OTHER condition, and the inverse results were observed for the SELF condition. Taken together, these results suggest that relative economic hardship may act as a motivating operation affecting social discounting with the potential for further translational utility.